Development and Evaluation of a Bicistronic DNA Vaccine against Nervous Necrosis Virus in Pearl Gentian Grouper (Epinephelus lanceolatus × Epinephelus fuscoguttatus) - Tianwen Lin; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Vaccines, 2022)
Nervous necrosis virus (NNV) can cause enormous economic losses in mariculture. Vaccines are promising ways to control the disease. In this study: the interferon regulatory factor 3 (IRF3) gene of pearl gentian grouper was cloned and functionally analyzed; then a bicistronic DNA vaccine encoding both capsid protein (CP) and IRF3 was constructed; then the cellular, humoral, and local immune responses in the grouper after immunization were investigated; and then the protective effects after the NNV challenge were investigated. The results showed that the vaccine successfully expressed CP and IRF3. After immunization, the lymphocytes were recruited at the injection site in the muscles. The percentage of sIgM+ lymphocytes in the head, kidney, and spleen significantly increased and peaked at 28.8 ± 3.1% and 42.6 ± 4.2% at the 3rd to 4th weeks. Six immune-related genes were significantly up-regulated. In the meantime, the total antibodies, anti-NNV specific antibodies, and neutralizing antibody titers in serum increased. After the challenge with 105, 106 or 107 TCID50/fish, the relative percent survival rate was 81.25%, 73.91%, and 66.67%, respectively. In 106 TCID50/fish groups, the percentages of sIgM+ lymphocytes, antibodies, and the viral load were investigated. In conclusion, the bicistronic vaccine significantly induced humoral and cellular responses in pearl gentian grouper and provided effective protection against NVV infection.